Advances in Smelting Reduction for Iron Making - Jouhari A.K.; Gupta R.C.; Ray H.S. (My University, 2025)
This paper gives present state of technology development for direct liquid ironmaking using coal. Foaming and kinetics are two important aspects to be properly understoodfor optimum productivity of a melter gasifier unit used in smelting reduction process. A brief critical review of researches in this area is given. The authors have carried out experimental investigations in this area and developed correlations between foaming and slag properties like density, viscosity and surface tension.